Novel Bioceramic Urethral Bulking Agents Elicit Improved Host Tissue Responses in a Rat Model - Travis K. Mann-Gow; Benjamin J. King; Ahmed El-Ghannam; Christine Knabe-Ducheyne; Masatoshi Kida; Ole M. Dall; Jan Krhut; Peter Zvara (Advances in Urology)
Objectives. To test the physical properties and host response to the bioceramic particles, silica-calcium phosphate (SCPC10) and Cristobalite, in a rat animal model and compare their biocompatibility to the current clinically utilized urethral bulking materials. Material and Methods. The novel bulking materials, SCPC10 and Cristobalite, were suspended in hyaluronic acid sodium salt and injected into the mid urethra of a rat. Additional animals were injected with bulking materials currently in clinical use. Physiological response was assessed using voiding trials, and host tissue response was evaluated using hard tissue histology and immunohistochemical analysis. Distant organs were evaluated for the presence of particles or their components. Results. Histological analysis of the urethral tissue five months after injection showed that both SCPC10 and Cristobalite induced a more robust fibroblastic and histiocytic reaction, promoting integration and encapsulation of the particle aggregates, leading to a larger bulking effect. Concentrations of Ca, Na, Si, and P ions in the experimental groups were comparable to control animals. Conclusions. This side-by-side examination of urethral bulking agents using a rat animal model and hard tissue histology techniques compared two newly developed bioactive ceramic particles to three of the currently used bulking agents. The local host tissue response and bulking effects of bioceramic particles were superior while also possessing a comparable safety profile.